Geological Features and Deformational Ages of the Basal Thrust Belt of the Miaowan Ophiolite in the Southern Huangling Anticline and Its Tectonic Implications - 蒋幸福 彭松柏 王璐 王军鹏 邓浩 (Journal of earth science (Wuhan, China), 2012)
The stratigraphic, structural and metamorphic features of the basal thrust belt of the ca. 1.0 Ga Miaowan （庙湾） ophiolite in the southern Huangling （黄陵） anticline, show that it can be divided into three tectono-lithostratigraphic units from north to south： mélange/wildflysch rock units, flysch rock units, and sedimentary rock units of the autochthonous （in situ） stable continental margin. The three units underwent thrust-related deformation during emplacement of the Miaowan ophiolitic nappe, with kinematic indicators indicating movement from the NNE to SSW, with the metamorphic grade reaching greenschist-amphibolite facies. LA-ICP-MS U-Pb geochronology of zircons from granite pebbles in the basal thrust-related wildflysch yield ages of 859±26, 861＋12 and 871±16 Ma; whereas monzonitic granite clasts yield an age of 813±14 Ma. This indicates that the formation age of the basal thrust belt is not older than 813±14 Ma, and is earlier than the earliest formation time of the majority of the Neoproterozoic Huangling granitoid intrusive complex, which did not experience penetrative ductile deforma-tion. These results suggest that the northern margin of the Yangtze craton was involved in collisional tectonics that continued past 813 Ma.This may be related to the amalgamation of the Yangtze craton with the Rodinia supercontinent. Through comparative study of lithology, zircon geochronology, REE patterns between granodiorite and tonalite pebbles in the basal thrust-zone conglomerate, it can be concluded that the pebbles are the most similar to the Huanglingmiao （黄陵庙） rock-mass （unit）, implying that they may have come from Huanglingmiao rock-mass. Zircon cores yield xenocrystic ages of 2 074±120 Ma, suggesting that the protolith of the Neoproterozoic Huangling granitoid intrusive complex may have originated from par-tial melting of older basement rocks, that is to say there may be Paleoproterozoic crystalline basement in the southern Huangling anticline. The ages of xenocrystic zircons in the granite pebbles in the basal-thrust congiomerate/wildflysch show a correlation with the age spectra from Australia, implying that the terrain that collided with the northern margin of the Yangtze craton and emplaced the Miaowan ophiolite at ca. 813 Ma may have been derived from the Australian segment of Rodinia.